2020
DOI: 10.3389/fgene.2020.578002
|View full text |Cite
|
Sign up to set email alerts
|

CD52 Is a Prognostic Biomarker and Associated With Tumor Microenvironment in Breast Cancer

Abstract: Tumor microenvironment (TME) plays an essential role in the development and metastasis of breast cancer (BC). More studies are needed on the differences and functions of immune components and matrix components. In this study, we calculated the proportion of tumorinfiltrating immune cells (TICs) and the proportion of immune and matrix components of BC patients from The Cancer Genome Atlas (TCGA). We performed Cox regression analysis and constructed protein-protein interaction (PPI) network based on the differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 26 publications
2
25
0
Order By: Relevance
“…Further analysis demonstrated that CCL19, CD3E, and ITK were not strongly associated with OS in our sample. However, previous research demonstrated that CD52 can play a significant prognostic role in BRCA patients (23). CD2 is an essential component in the immunological synapse, the actin cytoskeleton, and agonistic cell signaling, and it is expressed on the surface of T, NK, and dendritic cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…Further analysis demonstrated that CCL19, CD3E, and ITK were not strongly associated with OS in our sample. However, previous research demonstrated that CD52 can play a significant prognostic role in BRCA patients (23). CD2 is an essential component in the immunological synapse, the actin cytoskeleton, and agonistic cell signaling, and it is expressed on the surface of T, NK, and dendritic cells (24).…”
Section: Discussionmentioning
confidence: 99%
“…It is the target of the monoclonal antibody therapy alemtuzumab in several diseases including chronic lymphocytic leukemia, cutaneous T‐cell lymphoma (CTCL), and multiple sclerosis (MS) 39 . In breast cancer stromal tissue, CD52 has been linked to an expression signature of poor outcome, 40,41 our results give further evidence of the potential of its overexpression as marker of immune cell invasion in breast tumors.…”
Section: Discussionmentioning
confidence: 58%
“…With the better understanding of the association between lncRNAs and the immune system (23,24), more and more evidence indicates that lncRNAs can not only act as diagnostic biomarkers, but also prognostic signatures for cancer patients. Several studies have focused on using coding genes and noncoding RNAs to construct models to assess the prognostic and diagnostic values for BRCA (25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%